El maltrato intrafamiliar y su incidencia en el rendimiento en los estudiantes de 8vo y 9no año de educación básica de la unidad educativa República del Ecuador de la ciudad de Machala Provincia de el Oro, periodo lectivo 2013-2014 - Benítez Pardo, Jesús Salomón (2014)
Domestic abuse is a problem that affects almost every household of Ecuador, this has a direct impact on the academic performance of students who make up these families should pay much attention to intra-family relationships with students, and are changing their behavior as it should, you cannot demand good performance if there are no problems in the house. Violence has many shades and is presented in various forms at home, sometimes people get used to shouting or pushing, claims, teasing, not realizing that this is abuse occurs within the home if we're talking about domestic abuse. Research has focused on domestic abuse and its impact on student performance in basic education of 8th and 9th grade education in the República de Ecuador School. Such research has the problem under study arises where assumptions, theoretical framework and contextual framework that has to do with the interpretation of research data plus the legal administrative framework with the items and codes in which this research is based is presented and then find the results of research in their respectiven tables, hypothesis testing finally the proposal, it should help mitigate the effects of the phenomenon studied, with a school for parents where socializing, communication and good treatment is reference point